Transition phase clothing strategies and their effect on body temperature and 100-m swimming performance - Galbraith, A.; Willmott, A. (European Journal of Sport Science, 2018)
Objective: Effective warm-ups are attributed to several temperature-related mechanisms. Strategies during the transition phase, preceding swimming competition, have been shown to prolong temperature-related warm-up effects. The purpose of this study was to evaluate the effects of two different clothing strategies during the transition phase, on subsequent 100-m maximal swimming performance. Methods: Nine competitive swimmers (3 female, 21 ± 3 yrs; 6 male 20 ± 2 yrs, mean performance standard 702 FINA Points, mean 100-m seasons best time 61.54 s) completed their own 30-min individual pool warm-up, followed by 7-min changing time and a 30-min transition phase, straight into a 100-m maximal effort time-trial. During the transition phase, swimmers remained seated, either wearing warm or limited clothing. Swimmers returned 1 week later, where clothing conditions were alternated. Results: Post-transition phase skin and core temperature remained higher in the warm clothing condition compared to the limited clothing condition (Mean Core: 36.90 ± 0.17°C, 36.61 ± 0.15°C, P < .01; Mean Skin: 33.49 ± 0.59°C, 31.94 ± 0.59°C, P < .01). One hundred-metre finish times were 0.6% faster in the warm clothing condition compared to the limited clothing condition (62.63 ± 7.69 s, 63.00 ± 7.75 s, P < .01). Conclusion: Wearing warm clothing during a 30-min transition phase improved swimming performance by 0.6%, compared to limited clothing.